Propriedades eletrônicas de nanofios semicondutores de Fosfeto de Zinco (Zn3P2) - Lombardi, Gustavo Aparecido (Universidade Federal de São Carlos, 2018)
Zinc phosphide Zn3P2 nanowires with excellent crystalline quality were grown using the Vapor-Liquid-Solid (VLS) method with gold nanoparticles as catalysts. Single nanowire based devices were fabricated with ohmic nickel contacts. Thermally activated and variable range hopping mechanisms were simultaneously identified from temperature dependent transport measurements, with the later being dominant. Energy levels at 197 meV , 47 meV and 15meV associated to Zn vacancies and interstitial P atoms were identified. Hopping radius were found to be 58 nm for 300 K. These results show how the presence of some degree of disorder drastically affects the transport of current through the nanowire. Photocurrent measurements revealed the material potential as light sensors. Current gains as high as 400% and 660% were measured for white light and 660 nm laser, respectively.
Keywords: Nanofios; Semicondutores; Transporte eletrônico; Fosfeto de Zinco; Nanowires; Semiconductors; Electronic transport; Zinc phosphide; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA